Protein engineering of Bacillus thuringiensis δ-endotoxin: Mutations at domain II of CryIAb enhance receptor affinity and toxicity toward gypsy moth larvae - Rajamohan, Francis (The National Academy of Sciences of the USA, 1996)
Substitutions or deletions of domain II loop residues of Bacillus thuringiensis δ-endotoxin CryIAb were constructed using site-directed mutagenesis techniques to investigate their functional roles in receptor binding and toxicity toward gypsy moth (Lymantria dispar). Substitution of loop 2 residue N372 with Ala or Gly (N372A, N372G) increased the toxicity against gypsy moth larvae 8-fold and enhanced binding affinity to gypsy moth midgut brush border membrane vesicles (BBMV) ≈4-fold. Deletion of N372 (D3), however, substantially reduced toxicity (>21 times) as well as binding affinity, suggesting that residue N372 is involved in receptor binding. Interestingly, a triple mutant, DF-1 (N372A, A282G and L283S), has a 36-fold increase in toxicity to gypsy moth neonates compared with wild-type toxin. The enhanced activity of DF-1 was correlated with higher binding affinity (18-fold) and binding site concentrations. Dissociation binding assays suggested that the off-rate of the BBMV-bound mutant toxins was similar to that of the wild type. However, DF-1 toxin bound 4 times more than the wild-type and N372A toxins, and it was directly correlated with binding affinity and potency. Protein blots of gypsy moth BBMV probed with labeled N372A, DF-1, and CryIAb toxins recognized a common 210-kDa protein, indicating that the increased activity of the mutants was not caused by binding to additional receptor(s). The improved binding affinity of N372A and DF-1 suggest that a shorter side chain at these loops may fit the toxin more efficiently to the binding pockets. These results offer an excellent model system for engineering δ-endotoxins with higher potency and wider spectra of target pests by improving receptor binding interactions.